IS FINANCIAL RISK A BARRIER TO THE IMPLEMENTATION OF SDGS IN LOCAL GOVERNMENTS? AN ANALYSIS FOR SPANISH MUNICIPALITIES (Lex localis - Journal of Local Self-Government, 2025)
Local entities have a fundamental role in sustainable development and must design policies and strategies to achieve the Sustainable Development Goals (SDGs).This paper analyzes the possible impact of the financial condition on the achievement of the SDGs in Spanish local entities, developing a financial risk indicator for each government. The paper takes into account both the static and dynamic situation, that is the level for each government in two different years in the implementation of SDGs and the evolution between the two years, aiming at verifying whether the evolution of the financial condition goes hand in hand with the degree of implementation of the SDGs.In order to test it, univariate and multivariate analysis are carried to analyze the effect of the dimensions of the financial condition and of the financial condition itself on the level of implementation of the SDGs.